2007
DOI: 10.1084/jem.20070318
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of B cell homeostasis and activation by the tumor suppressor gene CYLD

Abstract: B cell homeostasis is regulated by multiple signaling processes, including nuclear factor-κB (NF-κB), BAFF-, and B cell receptor signaling. Conditional disruption of genes involved in these pathways has shed light on the mechanisms governing signaling from the cell surface to the nucleus. We describe a novel mouse strain that expresses solely and excessively a naturally occurring splice variant of CYLD (CYLDex7/8 mice), which is a deubiquitinating enzyme that is integral to NF-κB signaling. This shorter CYLD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
110
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 31 publications
1
110
2
2
Order By: Relevance
“…Jin and colleagues (29) found massive hyperplasia and expansion of marginal zone B cells in CYLD-deficient mice and increased responses of CYLD-deficient B cells in response to activation. Similar effects were caused by the expression of a truncated CYLD lacking exons 7 and 8 (30). However, in another study, CYLD deficiency did not affect peripheral B cell numbers, but increased NF-kB activation after stimulation (31).…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Jin and colleagues (29) found massive hyperplasia and expansion of marginal zone B cells in CYLD-deficient mice and increased responses of CYLD-deficient B cells in response to activation. Similar effects were caused by the expression of a truncated CYLD lacking exons 7 and 8 (30). However, in another study, CYLD deficiency did not affect peripheral B cell numbers, but increased NF-kB activation after stimulation (31).…”
mentioning
confidence: 67%
“…In the resulting CD19Cre/A20 1A) (30). CYLD-deficient mice were also intercrossed with CD19cre mice to control for the heterozygous ablation of CD19 and the expression of the Cre recombinase.…”
Section: Loss Of Cyld Does Not Exacerbate the Defects In A20-deficienmentioning
confidence: 99%
“…NF-κB1 (p105/p50) and NF-κB2 (p100/p52) need to be processed to become active and translocate to the nucleus where they associate with RelA (p65), c-Rel and RelB in different hetero-and homodimers to form the transcriptionally active complex. 16 Mice deficient in RelB show reduced numbers of MZ B cells, 17 whereas mice lacking a negative regulator of NF-κB have more MZ B cells 18 similar to mice that lack the inhibitory p100 subunit of NF-κB2. 19 We therefore quantified the abundance of all NF-κB proteins in the cytosol and the nucleus by immunoblotting of subcellular fractions obtained from freshly isolated splenocytes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, impaired CYLD expression is associated with immune diseases like inflammatory bowel disease (13). However, a number of recent studies in different mice bearing obligatory null alleles demonstrated putative, essential, yet contrasting roles for CYLD in the regulation of adaptive and innate immune responses (14)(15)(16)(17)(18). A first report aimed to eliminate CYLD functions in the mouse through the germ-line removal of the ATGcontaining exon 2 from the murine Cyld locus (15).…”
mentioning
confidence: 99%